Comprehensive optimization of PV inverter reactive and real power flows in unbalanced four wire LV distribution network operations - Su, Xiangjing; Masoum, Mohammad Sherkat; Wolfs, Peter (IEEE, 2013)
Roof top PV installations are normally not controlled by the network operator but driven by consumer actions. Some power quality issues have been caused or aggravated, such as voltage rise and unbalance which restricts further PV connections. However, the latent reactive power capability of PV inverters may be utilized to provide voltage/VAR support and increase the renewable power fraction. This paper proposes a novel three-step PV control strategy based on the reactive power control of inverters and real power curtailment. The optimization model is solved by a Sequential Quadratic Programming (SQP) based global approach and the validity is tested on a real 3-phase 4-wire unbalanced distribution network model developed during the Perth Solar City trial in Western Australia.